Penyusunan Bahan Makanan Keluarga Penderita Penyakit Hiperkolesterolemia Menggunakan Algoritme Genetika - Sabrina Nurfadilla; Imam Cholissodin; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
To improve the quality of human resource generation required good nutritional needs for everybody. Each member of family needs a nutrition in the same kind but amount of the nutrition is different, that is influenced by age, body shape, gender, physical condition, genetic heredity, and life style. Information of data analysis from Riskesdas which is held in 2007 and 2013 revealed that Indonesian citizen Having problems with quality food consumption of between 80 to 90 percent tend to be less fruit and/or vegetable consumption and approximately 40.7% consume risky foods containing excess fat, cholesterol and fried more than equal to one time per day. From these data nutritional needs with food processing which is consumed by Indonesian citizen still lack. Therefore, the preparation of family food ingredients of patients with hypercholesterolemia using genetic algorithms needed for food ingredients that are consumed are variety and able to meet the nutritional needs with minimal cost. Genetic algorithm is a stochastic optimization technique because using random value. Genetic algorithms are capable of providing complex and wide-ranging problem solutions objectively. In crossover process using extended intermediate method and mutation process using random mutation method. The best solution results obtained when the population size of 100, crossover rate of 0.8, mutation rate of 0.2, permutation limit value of 115 and generation of 65.